Indeks Penulis Volume 33, Tahun 2013 - Indeks Penulis Volume 33, Tahun 2013 (agriTECH, 2013)
Agustina, R. 101Anasta, N. 303Andriani, M. 288Anugrahwati, M. 189Apituley, D.A.N. 162Aprilita, N.H. 189Arahman, N. 32Arif, S.S. 112Ariviani, S. 324Assagaf, M. 16